Keindahan dalam Hikayat Sultan Taburat - Adilah Nurul Hidayah (Masyarakat Pernaskahan Nusantara, 2020)
Hikayat Sultan Taburat written by Muhammad Bakir. It is one of adventure stories which is also included in the type of solace tale. This research used transliteration of Hikayat Sultan Taburat ML 259 version from Rias Anto Suharjo in 2019. It has a dominant aesthetic elements and function in it. Malay aesthetic theory by Bragunsky used to be able to reveal those purpose. The various elements of external aesthetic in Hikayat Sultan Taburat could be identified through the description of the beauty of clothing, the charm of the princess, garden, music, reception, warfare, ship, and the crowds of the country. The function of external aesthetic in Hikayat Sultan Taburat is to entertain the reader. === Hikayat Sultan Taburat merupakan hikayat karangan Muhammad Bakir. Hikayat ini merupakan salah satu cerita petualangan yang juga termasuk dalam jenis cerita pelipur lara. Penelitian ini memakai transliterasi Hikayat Sultan Taburat versi ML 259 oleh Rias Anto Suharjo pada tahun 2019. Hikayat Sultan Taburat memiliki unsur dan fungsi keindahan yang dominan di dalamnya. Teori estetika Melayu oleh Braginsky dipakai untuk dapat mengungkapkan keduanya. Berbagai unsur keindahan dapat ditemukan melalui penggambaran keindahan pakaian, pesona tuan putri, taman, musik, periringan, peperangan, kapal, dan keramaian negeri. Fungsi keindahan dalam Hikayat Sultan Taburat berfungsi sebagai pelipur lara bagi pembacanya.